FABRICATION AND CHARACTERISATION OF FLEXIBLE STRAIN SENSOR BASED ON HYBRID 3D GRAPHENE/MXENE FOR MOTION DETECTION - AB ALIM, NIK NURUL NAZIPAH (2019)
The demand for wearable sensors in practical applications such as health monitoring, sports performance, smart textiles, and electronic skin is increasing yearly. Current approaches using elastomeric-based nanostructure matrices such as carbon nanotubes integrated with polydimethylsiloxane provides the flexibility and stretchability but suffers from various drawbacks such as liquid leakage during strain, agglomeration, and low dispersion. An elegant approach of incorporating graphene and MXenes with polydimethylsiloxane as thin film for the detection of human motion such as the movement of fingers, bending of elbows and walking is demonstrated. Graphene and MXenes were synthesised using chemical vapour deposition and selective etching techniques, respectively.